LITOFASIES ENDAPAN KUARTER DI WILAYAH DKI JAKARTA - Listyono, Girlly Marchlina; Arfiansyah, Kurnia; Natasia, Nanda; Alfadli, Muhammad Kurniawan; Pranantya, Pulung Arya (Bulletin of Scientific Contribution, 2016)
Bay of Jakarta is covered of Qartenary deposits with terrestrial deposits intercalation with marine deposits. Interaction between those depositional environment produce deposits which have lithofacies variation. Rapid development of Jakarta impact on impossibility in finding outcrop. This research gives changes for detailed Quarternary deposit lithofacies study through 22 wells with depth range about 120-450 metres and depth total 6.556,61 metres. Terrestrial deposit characterized by domination of relatively coarse clastics and content of remaining roots, woods, plants, high content of quartz, lithic fragment, calcareous and oxidated appearace. Marine deposit characterized by finer clastics, contain remain of shells, fosil, coral, limestone fragments, glauconites, calcareous. The lithofacies variation of Quartenary depost from the wells indicate lateral and vertical variation change, also on coastline shifting either by transgression or regression.       Keywords : deposits, Jakarta, quartenary, sediment Jakarta merupakan daerah teluk yang tersusun oleh endapan kuarter dengan karakteristik litologi yang beragam. Sedimen penyusun endapan kuarter Jakarta dipengaruhi oleh proses sedimentasi lingkungan pengendapan darat dan laut. Interaksi antara dua lingkungan pengendapan tersebut menghasilkan endapan yang memiliki variasi litofasies. Dengan pesatnya pembangunan di Jakarta menjadikan kesempatan untuk melihat singkapan sangat kecil. Penelitian ini memberikan kesempatan untuk melihat litofasies endapan kuarter Jakarta dengan lebih jelas melalui 22 sumur bor dengan kedalaman berkisar 120 – 450 meter dan total tebal 6.556,61 meter. Endapan darat dicirikan oleh dominansi klastika yang relatif kasar dan kandungan sisa akar, kayu, tumbuhan, kaya butiran kuarsa, fragmen litik, kerikilan, serta sifat karbonatan dan kenampakan teroksidasi. Batas antara keduanya sepanjang periode Kuarter memperlihatkan variasi secara vertikal dan lateral dan perubahan garis pantai baik transgresi maupun regresi. Kata Kunci : endapan, Jakarta, kuarter, sedimen